Twitter, social movements, and claiming allies in abortion debates. Issue 4 (2nd October 2019) - Hunt, Kate
ABSTRACT: Pervasive use of social media as a communication technology has allowed social movement organizations to more easily claim allies, especially public figures, to amplify their messages in the public sphere. This research utilizes the contentious debate over abortion rights in Ireland surrounding the 2018 referendum on abortion to examine the social media tactics by both anti- and pro-abortion organizations on Twitter. Previous research is suggestive that movements can easily claim outspoken public figures on Twitter, but social movement research suggests that movements may target certain allies more frequently than others. This study finds that what types of public figures movement organizations claim as allies by "retweeting" them on Twitter depends on social movements' position relative to the legal status quo of abortion in Ireland, pre-referendum.